Fraud Disclosure: A Systematic Literature Review Approach - Putri, Novia Septiana; Saifudin, Saifudin; Trilestari, Rr.Dian Indriana (Solusi, 2024)
Financial fraud is an issue of increasing concern in various sectors, especially in the context of companies and financial institutions. This article aims to explore the published literature on fraud disclosure. Using a systematic literature review approach, this article aims to identify, assess, and synthesize previous research results related to this topic. The systematic literature review approach allows researchers to follow a structured procedure in searching, selecting, and analyzing relevant literature. This process includes searching major academic databases, using specific keywords, and applying strict inclusion and exclusion criteria. The result of this process is a collection of the most relevant and high-quality studies that provide deep insights into the topic of fraud disclosure. This article identifies several key themes in the literature on fraud disclosure. First, there are various methods and techniques used to detect and report fraud, including Forensic Audit; Audit Investigation; Auditor Competence. Second, the article highlights the importance of transparency and responsibility in the fraud disclosure process, as well as the role of regulators and oversight bodies in overseeing this practice. Third, factors such as Forensic Auditing; Investigative Auditing; Auditor Competence also influence the extent to which and how fraud is disclosed. In addition, this article identifies some of the challenges faced in research on fraud disclosure, including data limitations, difficulties in measuring the effectiveness of various disclosure methods, and variability in applicable regulations. The conclusion of this review emphasizes the need for further research to develop a more comprehensive and effective framework for addressing fraud, as well as the importance of collaboration between academics, practitioners, and regulators to improve fraud disclosure practices.